Selecting environmental indicators for sustainable smart Cities Mission in India - Singh P.K.; Shruti; Ohri A. (My University, 2025)
Government of India (GOI) initiated Smart Cities Mission in June 2015. In order to guide the process, evaluate the performance, and finally move towards making a Sustainable Smart Cities program, the objective is to develop software based Environmental Decision Support System for Sustainable Smart Cities in India (EDSS-SSCI). Identification and finalization of indicators to be used in the framework for evaluation of Sustainable Smart Cities in Indian context is the objective of the present study. The analyses indicate that Smart Cities Mission guidelines of GOI include 14 performance parameters related with environment, out of which 11 qualify the criteria required for being considered as environmental indicator as per World Bank Environment Development (WBED) considerations and 3 of them do not meet the requirements in terms of clarity of design and quantification for development costs. Further, a set of 20 additional environmental performance indicators are identified from the available literatures on requirements of Sustainable Cities, many of which are generally used as monitoring parameters in various programs of GOI. Subjecting these 20 additional indicators for suitability as environmental indicators based on WBED criteria and City Key Indicators criteria, results in finalizing a set of 13 indicators which meet all requirements and qualify to be used in development of framework for EDSS-SSCI. 10 of these indicators are already part of monitoring programs of Ministry of Urban Development (MoUD), 2 have been suggested by Bureau of Standards (BIS 2016) and 1 considered important by Japan International Corporation Agency (JICA 2016). Thus, taking 11 environmental indicators from Smart Cities Mission Guidelines and 13 selected indicators for Sustainable Cities, a total of 24 environmental indicators are finalised to be used in the framework of EDSS-SSCI for benchmarking, performance evaluation and guiding the investment plans for most effective resource utilization under Indian conditions. © 2020 Technoscience Publications. All rights reserved.